2018
DOI: 10.1007/s10236-018-1206-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tidally induced larval dispersal over Anton Dohrn Seamount

Abstract: Massachusetts Institute of Technology general circulation model is used for the analysis of larval dispersal over Anton Dohrn Seamount (ADS), North Atlantic. The model output validated against the in situ data collected during the 136th cruise of the RRS 'James Cook' in May-June 2016 allowed reconstruction of the details of the baroclinic tidal dynamics over ADS. The obtained velocities were used as input data for a Lagrangian-type passive particle tracking model to reproduce the larval dispersal of generic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…When the ocean flow impinges on a seamount, a series of complex dynamic responses are generated that modulate local and large‐scale circulation (Lavelle & Mohn, 2010; Perfect et al, 2018, 2020a, 2020b; Robertson et al, 2017; White & Mohn, 2004). These dynamic processes around the seamount also contribute to local biological and geological distribution (Boehlert & Genin, 1987; Genin, 2004; Mitchell et al, 2015; Stashchuk et al, 2018; Vlasenko et al, 2018; White & Mohn, 2004; White et al, 2007). Hence, local circulation induced by the seamount topography is important to the energy and material exchanges in the deep ocean.…”
Section: Introductionmentioning
confidence: 99%
“…When the ocean flow impinges on a seamount, a series of complex dynamic responses are generated that modulate local and large‐scale circulation (Lavelle & Mohn, 2010; Perfect et al, 2018, 2020a, 2020b; Robertson et al, 2017; White & Mohn, 2004). These dynamic processes around the seamount also contribute to local biological and geological distribution (Boehlert & Genin, 1987; Genin, 2004; Mitchell et al, 2015; Stashchuk et al, 2018; Vlasenko et al, 2018; White & Mohn, 2004; White et al, 2007). Hence, local circulation induced by the seamount topography is important to the energy and material exchanges in the deep ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The great performance of the MITgcm on replication of internal tides was already checked and reported in many papers (e.g., Vlasenko et al, 2013Vlasenko et al, , 2014Vlasenko et al, , 2016Stashchuk et al, 2014Stashchuk et al, , 2018. These publications have shown the consistency of the observational data sets and the modeling outputs.…”
Section: The Modelmentioning
confidence: 78%
“…The experiments were restricted by 1,400 m depth. The spatial step between the position of the released particles was 450 m. The output model velocities were used as an input data set for the Lagrangian-type passive particle tracking model (Stashchuk et al, 2018) to reproduce the pathway of larvae from their initial position. In setting the time scale for the larvae spreading experiments, we followed the results of Larsson et al (2014) who showed that 50 days is the most real lifetime for larvae to be dispersed.…”
Section: Larvae Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated the feasibility of such a high-resolution unstructured grid model in accommodating very complex bathymetry and coastline, and in providing quantitative assessments of the modified circulation useful for local planning and management. Stashchuk et al (2018) tracked passive particles using currents from a general circulation model to simulate larval dispersal over the Anton Dohrn Seamount in the North Atlantic Ocean. The simulation shows that the majority of particles remains in the same depth band where they were initially released, suggesting that physical circulation processes, e.g., baroclinic tidal currents, may provide a potential isolating mechanism for the larvae; onlỹ 10% of particles can undergo maximum dispersal with successful recruitment to the benthos.…”
mentioning
confidence: 99%